Penerapan Model Pembelajaran Kooperatif Tipe STAD Mata Kuliah Sosiologi Sastra di Perguruan Tinggi Berbasis Analisis Unsur Sosial Novel Ayah - Madyananda, Ulinnuha; Rakhmawati, Ani (Adjektiva: Educational Languages and Literature Studies, 2022)
This research is a descriptive qualitative research that aims to implement the STAD type cooperative learning model with a combination of the results of the analysis of the social elements of Ayah novel in the literature sociology course in college. The purpose of this study was to (1) know how to model STAD learning with a combination of the results of the analysis of the social elements of Ayah novel effective or not when applied in learning to learn the sociology of literature in universities and (2) find out how to use the results of the social analysis of Ayah novel in learning literary sociology in college. The research method used is descriptive qualitative with content analysis method and index interview. The source of this research data includes the text of Ayah novel, interview guide, and syllabus of learning sociology of literature. Data collection techniques by analyzing documents and interviews in depth. Checking the validity of the findings using source, method and theory triangulation by checking document data and interview results to get the same conclusion. The sampling technique used was purposive sampling while data analysis techniques used interactive model analysis of three components, namely data reduction, data presentation, and conclusion. The results of the analysis showed that the application of the STAD type cooperative learning model with a combination of the results of Ayah novel social element analysis in the literature sociology courses in universities was effective if applied in group-based learning (cooperative).